COVID-19 Paradox: The Role of Privacy Concerns and Ad Intrusiveness on Consumer’s Attitude Toward App Usage Behavior - Bano, Sobia; Sarfraz, Usama; Salameh, Anas A.; Jan, Amin (Frontiers in Psychology, 2022)
The COVID-19 pandemic has changed lives in an unprecedented way. The most notable and urgent requirement to combat the epidemic was to transform the way human interacts with each other. The adherence to maintaining social distance has given an upsurge to the increased usage of Mobile app users. This change in human interaction for fulling their basic to social to work needs through the intervention of app usage has led to privacy concerns by users. By keeping in view the changing dynamics of the way society works, this study is an endeavor to investigate gender differences of ad intrusive and privacy concerns on app usage behavior. Employing a quantitative research design, 371 respondents were surveyed using an online structured questionnaire. Data were analyzed by using Partial Least Square Structural Equation Modelling (PLS-SEM). Results suggest that advertising intrusiveness and privacy concerns are significant in determining the consumer's attitude towards App usage and a positive attitude towards App usage results in App usage behavior. However, gender’s moderating role in attitude towards app usage and app usage behavior is insignificant for this study. The study provides a more comprehensive understanding and complements prior insights on ads intrusiveness and privacy concerns towards app usage.